POTENSI JERAMI PADI SEBAGAI PAKAN SAPI POTONG DI KABUPATEN REMBANG - Dwi Retno Lukiwati; Rina Muryani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
The availability and quality of fodder resources is the principal constraint to cow cattle production. The fodder available usually include grasses, legumes and crops residues such as straw of paddy rice. The objective for the observation research is to study the production and potency of paddy rice straw as beef cattle fodder, using survey method, in Rernbang Regency: Data were col.lected through interviewing using structured questionnaires with 66 respondents in 3 district: Kragan, Pamotan and Surnber, for 6 months. Data of production and potency of paddy rice straw were analyzed by usual method. The result showed that population of cow cattle inyear2004 was 95.288 head, which increased in the first 3 months of2005 co be IO 1.634 head. The potency of the paddy rice straw for beef cattle fodder was 46,23% in 2004, whereas in 2005 was 43,02%. As conclusion, the availability and quality of cow canle fodder which is very low in the dry season will affect the productivity of cow cattle.